(untitled) (Світ фінансів, 2017)
Петрущак Б. Вплив екзогенних чинників на розвиток українського фондового ринку. Розкрито вплив міжнародних фондових ринків на розвиток українського фондового ринку. Визначено річні, квартальні, місячні та тижневі коефіцієнти кореляції. Проаналізовано зв’язок між фондовими ринками у короткостроковому і довгостроковому періодах. Petrushchak B. The influence of the exogenous factors on the development of Ukrainian stock market. The influence of international stock markets on the Ukrainian stock market is examined. The yearly, quarterly, monthly and weekly coefficients of correlation are determined. The relation between stock markets in short and long run is analyzed.